Two crafty criminals! : and how they were captured by the daring detectives of the New Cut Gang ; including Thunderbolt's Waxwork & the gas-fitters' ball - Pullman, Philip, 1946- (Alfred A. Knopf, 2012)
Eleven-year-old Benny Kaminsky leads a rag-tag gang of neighborhood children as they use improbable disguises and crazy ruses while investigating such crimes as counterfeiting and stolen silver in 1894 London.